2007
DOI: 10.1111/j.1464-410x.2007.07016.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low dose‐rate prostate brachytherapy on the sexual health of men with optimal sexual function before treatment: analysis at ≥ 7 years of follow‐up

Abstract: OBJECTIVE To evaluate the effect of low‐dose rate prostate brachytherapy on the sexual health of men with ≥ 7 years of prospective evaluation and optimum sexual function before treatment. PATIENTS AND METHODS In all, 223 patients with T1b to T3a prostate cancer and a median (range) age of 66  (50–82) years were treated with permanent seed implantation from November 1990 to March 1998. They were followed for a median (range) of 8.2 (7–14.1) years using prospective quality‐of‐life measures. Erectile function (EF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
2
3

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 26 publications
4
20
2
3
Order By: Relevance
“…Although an assessment of toxicity was not the main objective of this report, young men appeared less likely to experience erectile dysfunction following BT than older men, a finding than has been previously reported by our group and others (37)(38)(39)(40), whereas the incidence of rectal and gastrourinary toxicity appeared similar between the two age groups.…”
Section: Discussioncontrasting
confidence: 55%
“…Although an assessment of toxicity was not the main objective of this report, young men appeared less likely to experience erectile dysfunction following BT than older men, a finding than has been previously reported by our group and others (37)(38)(39)(40), whereas the incidence of rectal and gastrourinary toxicity appeared similar between the two age groups.…”
Section: Discussioncontrasting
confidence: 55%
“…56 Patients aged less than 60 years and with optimal erectile function before brachytherapy have a high probability of long-term maintenance of the function. 57 Neo-adjuvant hormonal treatment, existence of supplemental EBRT, total radiation dose delivered to the prostate, and diabetes can be factors that induce post-brachytherapy erectile dysfunction. Brachytherapy-induced erectile dysfunction responds favorably to a phosphodiesterase 5 inhibitor (PDEI), 54 and its early use is associated with a signifi cant improvement and maintenance of erectile function.…”
Section: Treatment Morbiditymentioning
confidence: 99%
“…17 Various studies have reported erectile function outcomes after radical prostatectomy, 18 brachytherapy, 19 or external-beam radiotherapy with or without brachytherapy 20,21 using the IIEF-5. Many more studies have used the EPIC to assess ED in prostate cancer patients.…”
Section: Discussionmentioning
confidence: 99%